solve (2x-1)²d²y/dx²+(2x-1)dy/dx-2y=8x²-2x+3
Answers
Answered by
5
Answer:
On dividing the given equation by x^2, it becomes y'' - 2[(1+x)/x]y' + 2(1+x)y/x^2 = x, which is a second order linear differential equation of the form : y''+f(x)y'+g(x)y = r(x), where x.f(x) and (x^2).g((x) and r(x) are analytic at x=0, i.e. x=0, is a regular singular point of the equation. Accordingly we apply the Frobenius' Extended Power series method and put
y=Sigma(n=0 to inf.)(c_n)x^(n+k), in the original equation, where the coefficients c_n and the index k are to be determined by differentiating the above, twice with respect to x and by comparison of coefficients of x on the two sides of the equation
EAGERLY WAITING FOR THE BRAIENLIST CHOSSING
Answered by
4
Step-by-step explanation:
let z=log(2x-1)
from here e^z=2x-1
x=e^z+1/2
(2x-1)^2d^2
Attachments:
![](https://hi-static.z-dn.net/files/db4/f69b02cc4a19d4606b732b83dfab0954.jpg)
![](https://hi-static.z-dn.net/files/d40/44e4a2196197f0dd6df1dcf790268c17.jpg)
Similar questions